Implementation of Emotional Approach to Islamic Religious Education in SMP Masmur Pekanbaru - Rahman, Arini; Risnawati, Risnawati; Rizqa, Miftahir (AR-RASYID : Jurnal Pendidikan Agama Islam, 2024)
This study aims to analyze the application of emotional approach by educators in the field of Islamic Religious Education (PAI) at Masmur Junior High School Pekanbaru. The emotional approach focuses on managing positive relationships between educators and students, with the aim of creating a learning atmosphere that is conducive, comfortable, and supports students' psychological development. The research method used was qualitative with data collection techniques through interviews and observations. The results showed that the application of emotional approach in Masmur Junior High School Pekanbaru includes several strategies, such as introductory sessions, emotional support, the use of suggestion boxes, rewards for active students, and the application of educational games. In addition, this study also identified supporting and inhibiting factors in the implementation of this approach. Supporting factors include school management support, educator readiness, and good communication, while inhibiting factors include time constraints and learners' attitudes.